A new species of Neohydatothrips (Thysanoptera: Sericothripinae) from China - Zhang, Shi-Meng; Ban, Cheng-Jun; Feng, Ji-Nian; Yang, Mao-Fa (Zootaxa, 2023)
Neohydatothrips stachyurus sp. n. is described from Guizhou, China. Morphologically, this new Sericothripinae species is characterized by the shape of blotch on pronotum and the distribution of microtrichia on abdominal segments. The distribution of Neohydatothrips species from China also is discussed.